PEMENUHAN HAK PENYANDANG DISABILITAS PADA PERUSAHAAN SWASTA DALAM PERSPEKTIF HUKUM KETENAGAKERJAAN - Suryanto, Suryanto (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Persons with disabilities are everyone who experiences physical, intellectual, mental, and/or sensory limitations for a long period of time who in interacting with the environment can experience obstacles and difficulties to participate fully and effectively with other citizens based on equal rights. With these limitations, people with disabilities must get special attention by the state. So that in 2016 Law Number 8 of 2016 concerning Persons with Disabilities was issued. Problems that are often found include the obligation to employ 1% of people with disabilities in their companies, provide job security or social security, provide adequate accommodation, provide special assistance, provide decent salaries, and place appropriate work positions for people with disabilities. The formulation of the problem raised is whether the rights of persons with disabilities in private companies have been fulfilled based on labor law and what legal efforts can be made by persons with disabilities if their rights are not fulfilled in private companies according to labor law. This legal research method uses normative juridical with Doctrinal Research type, namely research sourced from applicable laws and regulations, court decisions, legal theories and concepts and the views of legal scholars. In its implementation, PT Wangta Agung applies Inclusive principles are a process for involving all people regardless of differences in background, condition or status. Legal efforts that can be made by workers with disabilities can be done through preventive legal efforts by making work agreements and providing occupational health and safety guarantees.